The Microenvironmental Effect in the Progression, Metastasis, and Dormancy of Breast Cancer: A Model System within Bone Marrow. (6th February 2012) - Reddy, Bobby Y.; Lim, Philip K.; Silverio, Kimberly; Patel, Shyam A.; Won, Brian Wong; Rameshwar, Pranela
Abstract : Despite diagnostic advances, breast cancer remains the most prevalent cancer among women in the United States. The armamentarium of treatment options for metastatic disease is limited and mostly ineffective with regards to eradicating cancer. However, there have been novel findings in the recent literature that substantiate the function of the microenvironment in breast cancer progression and the support of metastasis to tertiary sites such as bone marrow. The uncovered significance of the microenvironment in the pathophysiology of breast cancer metastasis has served to challenge previously widespread theories and introduce new perspectives for the future research to eradicate breast cancer. This paper delineates the current understanding of the molecular mechanisms involved in the interactions between breast cancer cells and the microenvironment in progression, metastasis, and dormancy. The information, in addition to other mechanisms described in bone marrow, is discussed in the paper.